2D Metal–Organic Framework Nanosheets based on Pd-TCPP as Photocatalysts for Highly Improved Hydrogen Evolution - Kim, Ji Hyeon; Wu, Siming; Zdrazil, Lukas; Denisov, Nikita; Schmuki, Patrik (Angewandte Chemie International Edition, 2024)
In this report, a 2D MOF nanosheet derived Pd single-atom catalyst, denoted as Pd-MOF, was fabricated and examined for visible light photocatalytic hydrogen evolution reaction (HER). This Pd-MOF can provide a remarkable photocatalytic activity (a H2 production rate of 21.3 mmol/gh in the visible range), which outperforms recently reported Pt-MOFs (with a H2 production rate of 6.6 mmol/gh) with a similar noble metal loading. Notably, this high efficiency of Pd-MOF is not due to different chemical environment of the metal center, nor by changes in the spectral light absorption. The higher performance of the Pd-MOF in comparison to the analogue Pt-MOF is attributed to the longer lifetime of the photogenerated electron-hole pairs and higher charge transfer efficiency.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Metal–Organic Frameworks; Pd Single Atom; Photocatalysis

Pt Single Atom Deposition by Direct Current Sputtering in the Gas-Scattering Regime—A Simple Approach to Controlled Single Atom Loading - Zhou, Xin; Kim, Ji Hyeon; Kim, Hyesung; Zahra, Sani; Schmuki, Patrik (Chemsuschem, 2025)
Supported single atoms represent a new frontier in many catalytic fields, and noble metal single atoms in particular have been reported to be a highly effective cocatalyst in photocatalysis or electrocatalysis. Herein, it is described that direct current sputtering of Pt, when operated under plain gas-scattering conditions, can be leveraged for single atom deposition on various substrates (herein TiO2 and graphene are used as examples). The approach allows a uniform single atom deposition with a high level of control over single atom density and loading amount on both surfaces. Such Pt single atoms on TiO2 can be used directly (without further treatments) as cocatalysts for photocatalytic H2 generation. Remarkably, single atom loading and H2 generation activity correlate linearly over a wide range of Pt loading (0.16–1.41 at%). The findings not only open a new avenue for the synthesis and use of single atoms in photocatalysis but also highlight the use of gas-phase scattering as a simple, scalable, and versatile approach for single-atom catalyst fabrication.
CRIS-Team Scopus Importer:2025-05-23
Keywords: hydrogen generation; photocatalysis; platinum; single-atom catalysis; sputter deposition

Pt Single Atoms Loaded on Thin-Layer TiO2 Electrodes: Electrochemical and Photocatalytic Features - Zhou, Xin; Wang, Yue; Denisov, Nikita; Kim, Hyesung; Kim, Ji Hyeon; Will, Johannes; Spiecker, Erdmann; Vaskevich, Alexander; Schmuki, Patrik (Small, 2024)
Recently, the use of Pt in the form of single atoms (SA) has attracted considerable attention to promote the cathodic hydrogen production reaction from water in electrochemical or photocatalytic settings. First, produce suitable electrodes by Pt SA deposition on Direct current (DC)-sputter deposited titania (TiO2) layers on graphene—these electrodes allow to characterization of the electrochemical properties of Pt single atoms and their investigation in high-resolution HAADF-STEM. For Pt SAs loaded on TiO2, electrochemical H2 evolution shows only a very small overpotential. Concurrent with the onset of H2 evolution, agglomeration of the Pt SAs to clusters or nanoparticles (NPs) occurs. Potential cycling can be used to control SA agglomeration to variable-size NPs. The electrochemical activity of the electrode is directly related to the SA surface density (up to reaching the activity level of a plain Pt sheet). In contrast, for photocatalytic H2 generation already a minimum SA density is sufficient to reach control by photogenerated charge carriers. In electrochemical and photocatalytic approaches a typical TOF of ≈100–150 H2 molecules per second per site can be reached. Overall, the work illustrates a straightforward approach for reliable electrochemical and photoelectrochemical investigations of SAs and discusses the extraction of critical electrochemical factors of Pt SAs on titania electrodes.
CRIS-Team Scopus Importer:2024-08-23
Keywords: anatase thin film electrode; electrocatalytic hydrogen evolution; graphene; photocatalytic hydrogen evolution; Pt Single atom